2020
DOI: 10.3390/cancers12030748
|View full text |Cite
|
Sign up to set email alerts
|

KLF5 Is Crucial for Androgen-AR Signaling to Transactivate Genes and Promote Cell Proliferation in Prostate Cancer Cells

Abstract: Androgen/androgen receptor (AR) signaling drives both the normal prostate development and prostatic carcinogenesis, and patients with advanced prostate cancer often develop resistance to androgen deprivation therapy. The transcription factor Krüppel-like factor 5 (KLF5) also regulates both normal and cancerous development of the prostate. In this study, we tested whether and how KLF5 plays a role in the function of AR signaling in prostate cancer cells. We found that KLF5 is upregulated by androgen depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Li et al showed that KLF5 was a key factor in androgen- AR signaling. It promoted the proliferation of PCa cells and could serve as a therapeutic target for PCa treatment (Li et al, 2020 ). As a famous star driving the carcinogenesis of PCa from normal prostate tissue to cancer biology, the AR signaling has already been explored across different researches, and the results in this study computationally demonstrated new insights and improved the understandings in AR -mediated PCa genesis.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al showed that KLF5 was a key factor in androgen- AR signaling. It promoted the proliferation of PCa cells and could serve as a therapeutic target for PCa treatment (Li et al, 2020 ). As a famous star driving the carcinogenesis of PCa from normal prostate tissue to cancer biology, the AR signaling has already been explored across different researches, and the results in this study computationally demonstrated new insights and improved the understandings in AR -mediated PCa genesis.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the genes such as ETS1 and FGFR1 have been reported to participate in the development of PCOS ( Song et al, 2019 ; Patil et al, 2020 ). Among the other genes, KLF5 is an important transcription factor that regulates androgen-AR signaling ( Li et al, 2020 ); CYP1B1, a dioxin-inducible oxidoreductase, is involved in the metabolism of estradiol ( Muneeb et al, 2014 ); IRS1 is an insulin receptor substrate gene that mediates the control of various cellular processes by insulin ( Kasch et al, 2018 ; Park et al, 2018 ). These genes were significantly enriched in biological processes of adipocyte differentiation, insulin resistance, female pregnancy, and circadian rhythm, indicating they are likely to be involved in pathogenesis of PCOS.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factors Krüppel-like factor 5 and 6 (KLF5 and KLF6) are critically involved in prostate cancer progression [ 386 , 387 ]. Recently, it was shown that KLF5 acetylation regulates luminal differentiation of basal progenitors in prostate development and regeneration [ 388 ] and is involved in TGFβ caused docetaxel resistance [ 389 ].…”
Section: Post-translational Modifications In Prostate Cancermentioning
confidence: 99%